Unemployment and crime: Differencing is no substitute for modelling - Hale, Chris (Journal of research in crime and delinquency, 1991)
The article gives the author's response to comments made by D. Cantor and K.C. Land to research carried out by the author and D. Sabbagh, on the relationship between unemployment and crime. The first defense that Cantor and Land give for a full structural model is that they and others have elsewhere estimated the U-C relationship within such a framework. Cohen and Land in 1987 found that unemployment has a negative contemporaneous effect for automobile theft but that its effect on murder rates is insignificant. Faced with the problem of estimating a full structural model to test their hypotheses, they claimed to be able to escape from the task by the simple device of splitting the independent variables, which might influence crime rates, into two groups. The first contained all variables apart from unemployment. According to Cantor and Land, these accounted for secular trends in crime rates. The second consisted of current and lagged unemployment. They caused crime rates to fluctuate around the trend. Hence on this assumption, all that is needed is to remove the trend from crime rates and what is left must be explained by unemployment